Notary’s executive inscription - Maxatov, N.R.; Zhamalbekova, A.S. (Bulletin of the Karaganda University “Law Series”, 2023)
In the article, the authors consider the work of a notary as an activity aimed not only at preventing legal conflicts, but also at assisting in resolving conflicts during the notary’s execution of an executive inscription. In this regard, the authors analyze the structure of the legal conflict, as well as the functional and procedural role of the notary in the process of resolving it. Executive inscription, according to the authors, is at the peak of its popularity, acting as an extrajudicial form, it (executive inscription) seeks to help in the restoration of those civil rights that have been subjected to violations, and for this purpose the mechanism is used to recover from debtors in favor of creditors money or property, and the main advantage is that the protection is carried out without mandatory recourse to the court. The theoretical elaboration of the notary’s executive inscription is little represented by the works of modern authors. The authors note that although a notary has the right to make an executive inscription according to the indisputable requirements of the creditor, nevertheless notaries practice this notarial action, but not without consequences for themselves.